Are Patients Willing to Ask for Generic Drug Substitutions? - Hermansyah, Andi (DRUNPP Association of SARAJEVO & HERZEGOVINA, BOSNIA, 2013)
Objective: Generic drug substitution has been known as a strategy to promote generic drug use. Under the pharmacy practice act, pharmacists in Indonesia are allowed to do generic substitution with the approval of a physician and/or the patients. This study was conducted to discover patients’ willingness to ask for generic drug substitutions. Methods: A study was carried out by surveying 300 respondents in Surabaya, Indonesia. A structured questionnaire was used to find out patients’ opinions and willingness regarding generic drug substitutions. The results were then analyzed by displaying the frequency of the respondents’ answers and their willingness to ask for generic drug substitutions. Results: The majority of the respondents recognized several characteristics of generic drugs properly but the emphasis was on the cheap price of the drug. Although they agreed that generic drug is a safe, effective and affordable drug, patients were not confident to ask for generic substitutions. They heavily relied on the advice of healthcare professionals for the substitutions. Conclusion: Although most of the respondents were willing to ask for generic substitutions, at the end they preferred to listen to professional advice from healthcare providers. Their willingness was mainly influenced by the preference of physicians and pharmacists; therefore, it is an opportunity for pharmacists to endorse patients to use generic drugs.